Reflecting on Twisted Thinking. New Insights into the Ideology of Right-Wing Totalitarianism - Harieta Mareci Sabol (Codrul Cosminului, 2018)
Generally, totalitarianism is presented as the opposite of democracy, although the two systems proclaim the same goal: „the good of the people/demos”. By this viewpoint, totalitarianism (left wing and right wing) derives from democracy as nothing more than a mutation. Concerning the nature of fascism, it is based on the exploitation of history, traditions, customs, but not in the interests of the demos, but of the new totalitarian elite. Thus, following the logical-explanatory line of viral metamorphism, it can be observed that the fundamental role in the ideological development of the extreme right played the „infection” of pluralistic political thinking with an irrational mentality, consisting of existentialism, intuitionism, vitalism, nihilism, symbolism, restoration of thought magical, archetypal, mystic, mystical, taboo-based.